Estudio de los recursos fitoterapéuticos ancestrales para su conservación y aprovechamiento sostenible”. “Aislamiento e identificación de metabolitos secundarios de la especie Artemisia absinthium - Villavicencio Reinoso, Marlon Bolivar (2014)
Using chromatographic techniques, GC-MS and GC-FID was determined composition chemistry of essential oil of the aerial parts of Artemisia absinthium collected in Catamayito-Catamayo (Ecuador). It was identified the presence of ten constituents, which represent 93.80% of the total oil. The major constituents of the oil were Sabinyl acetate (57.76%) and β-Thujone (20.65%), Sabinene (8.25%). The biological activity of the extracts obtained in Hexane, Ethyl Ether, Ethyl Acetate, Ethanol, Methanol, Water and essential oil was evaluated by the broth microdilution method. Ethyl Ether extract presented a minimum inhibitory concentration (MIC) against strains of Gram-negative, exhibiting MIC values of 15.62 μg/mL for S. aureus and 250 μg/mL for P. vulgaris in ether extract. Finally, the total phenolic content and antioxidant activity was determined by the DPPH and ABTS method